Atom probe examinations of Zircaloy irradiated at nominally 358 °C. (May 2019) - Cockeram, B.V.; Edmondson, P.D.; Leonard, K.J.; Kammenzind, B.F.; Hollenbeck, J.L.
Highlights: Zircaloy-2 and Zircaloy-4 were neutron irradiated at 358 °C in the high flux isotope reactor (HFIR) to a neutron fluence of 29.6 × 10 24  n/m 2 ( E  > 1 MeV) and the resultant irradiation hardening was measured by tensile testing. The measured irradiation hardening was closely related to the loop size and number density (ND) using an Orowan hardening model when the loops were assumed to be strong barriers like voids. In this work Atom Probe Tomography (APT) was used to detect the segregation and clustering of Fe, Sn, and Cr at features consistent with loops. The tendency for clustering of Fe, Sn, and Cr at loops could result in the apparent high barrier strength for these features. These clusters are also an additional hardening barrier. However, local variation in the distribution of clusters is observed from region to region in the irradiated material that appears to be related to factors such as the proximity to precipitates, local variations in microstructure, and/or microchemistry. Abstract : Zircaloy-2 and Zircaloy-4 were neutron irradiated at 358 °C in the high flux isotope reactor (HFIR) to a neutron fluence of 29.6 × 10 24  n/m 2 ( E  > 1 MeV) and the resultant irradiation hardening was measured by tensile testing. Irradiation at the relatively high temperature of 358  °C resulted in about 25–45% less hardening than observed in the literature for irradiations at 260–326  °C. The lower irradiation hardening was shown to result from a coarser loop distribution. The measured irradiation hardening was closely related to the 〈a〉 loop size and number density (ND) using an Orowan hardening model when the loops were assumed to be strong barriers like voids. In this work Atom Probe Tomography (APT) was used to detect the clustering of Fe, Sn, and Cr at features consistent with loops. The tendency for clustering of Fe, Sn, and Cr at loops could result in the apparent high barrier strength for these features. These clusters are also an additional hardening barrier. However, local variation in the distribution of clusters is observed from region to region in the irradiated material that appears to be related to factors such as the proximity to precipitates, local variations in microstructure, and/or microchemistry.